1998
DOI: 10.1128/mcb.18.5.2976
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-Dependent DNA Transactions in the Mitochondrial Genome of a Yeast Hypersuppressive Petite Mutant

Abstract: Mitochondrial DNA (mtDNA) of Saccharomyces cerevisiae contains highly conserved sequences, called rep/ori, that are associated with several aspects of its metabolism. These rep/ori sequences confer the transmission advantage exhibited by a class of deletion mutants called hypersuppressive petite mutants. In addition, because they share features with the mitochondrial leading-strand DNA replication origin of mammals, rep/ori sequences have also been proposed to participate in mtDNA replication initiation. Like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 50 publications
2
18
0
Order By: Relevance
“…In other words, the PSþ genome may be more rapidly replicated, contributing to its ability to suppress poly(A)-mediated mRNA instability. A possible parallel would be yeast petite strains, where large deletions in mitochondrial DNA are accompanied by amplification of the remaining sequences (Van Dyck and Clayton, 1998). Another possibility is that the PSþ genome fails to interact with nuclear gene products regulating genome dynamics.…”
Section: Dynamic Alteration Of Cpdna In Spa Strainsmentioning
confidence: 99%
“…In other words, the PSþ genome may be more rapidly replicated, contributing to its ability to suppress poly(A)-mediated mRNA instability. A possible parallel would be yeast petite strains, where large deletions in mitochondrial DNA are accompanied by amplification of the remaining sequences (Van Dyck and Clayton, 1998). Another possibility is that the PSþ genome fails to interact with nuclear gene products regulating genome dynamics.…”
Section: Dynamic Alteration Of Cpdna In Spa Strainsmentioning
confidence: 99%
“…However, a class of mtDNA deletion [rho Ϫ ] mutants, the hypersuppressive mitochondrial genomes (10), is stably maintained in cells lacking the gene encoding mitochondrial RNA polymerase (13,35). Maintenance of hypersuppressive genomes is also independent of factors such as the histone-like protein Ab2fp or the mitochondrial transcription factor Mtf1p (44 (31). Next, mtDNA was isolated from mdj1-5 cells grown at permissive and nonpermissive temperatures and separated from nuclear DNA in a cesium chloride gradient (Fig.…”
Section: Figmentioning
confidence: 99%
“…In support of this mechanism, each mtDNA replication origin shares sequence similarity with the heavy-strand replication origin of mammalian mtDNA, including the presence of a transcription promoter and three GC-rich clusters (2, 13). RNA synthesized by Rpo41 from mtDNA replication-origin promoters has been detected, and an endoribonuclease that cleaves the synthesized RNA at sites that correspond to regions of transition from RNA to DNA synthesis has been detected (3,49,53). The intact replication-origin promoter is required for hypersuppressiveness (36).…”
mentioning
confidence: 99%
“…The intact replication-origin promoter is required for hypersuppressiveness (36). However, this transcription-dependent process is not the sole mechanism for the initiation of mtDNA replication, since both the replication origin and RPO41 are dispensable for the maintenance of [rho Ϫ ] mtDNA (18,53). In addition, it has been reported that the selective inheritance of hypersuppressive [rho Ϫ ] mtDNA relative to nonhypersuppres-sive [rho Ϫ ] mtDNA (lacking a replication origin) is independent of RPO41 (34).…”
mentioning
confidence: 99%